How did modern morphology evolve in the human mandible? The relationship between static adult allometry and mandibular variability in Homo sapiens. Issue 157 (August 2021) - Bergmann, Inga; Hublin, Jean-Jacques; Gunz, Philipp; Freidline, Sarah E.
Abstract: Key to understanding human origins are early Homo sapiens fossils from Jebel Irhoud, as well as from the early Late Pleistocene sites Tabun, Border Cave, Klasies River Mouth, Skhul, and Qafzeh. While their upper facial shape falls within the recent human range of variation, their mandibles display a mosaic morphology. Here we quantify how mandibular shape covaries with mandible size and how static allometry differs between Neanderthals, early H. sapiens, and modern humans from the Upper Paleolithic/Later Stone Age and Holocene (= later H. sapiens ). We use 3D (semi)landmark geometric morphometric methods to visualize allometric trends and to explore how gracilization affects the expression of diagnostic shape features. Early H. sapiens were highly variable in mandible size, exhibiting a unique allometric trajectory that explains aspects of their 'archaic' appearance. At the same time, early H. sapiens share a suite of diagnostic features with later H. sapiens that are not related to mandibular sizes, such as an incipient chin and an anteroposteriorly decreasing corpus height. The mandibular morphology, often referred to as 'modern', can partly be explained by gracilization owing to size reduction. Despite distinct static allometric shape changes in each group studied, bicondylar and bigonial breadth represent important structural constraints for the expression of shape features in most Middle to Late Pleistocene hominin mandibles.